Two new species of Phaeoclavulina (Gomphaceae, Gomphales) from Hunan Province, China - Liu, Wen-Hao; Yan, Jun; Deng, Peng-Tao; Qin, Wei-Qiang; Zhang, Ping (Phytotaxa, 2022)
Two new species of Phaeoclavulina (Gomphaceae, Gompales, Basidiomycota) from Hunan Province, China are distinguished on the basis of the morphological characters and molecular phylogenetic analyses. Phaeoclavulina aeruginea is characterized by basidiomata ramarioid, repeatedly branched, stipe yellowish brown, copper-green and blunt branch tips, and the context, turning wine red when bruised or exposed. Phaeoclavulina cinnamomea produces the cinnamon basidiomata, crowded branches, and large basidiospores with truncate (volcanic) spines, which is particularly rare in Phaeoclavulina. The two species are illustrated by drawings and photographs, including scanning electron micrographs. Their taxonomic distinctness was supported by the phylogenetic analyses of internal transcribed spacer (ITS) and nuclear ribosomal large subunit (nrLSU) sequence data. The ITS and nrLSU sequences newly generated in this study were deposited in GenBank. A key to Phaeoclavulina species in China is provided.